Degradation High Concentration of Eosin Yellowish Dye in Heterogeneous Catalyst Solution - Ihab Abbas Taher (Journal of Global Pharma Technology, 2018)
Eosin yellowish was intended to be degraded by the use of photo catalysis process which is proposed to be mediated by ZnO and irradiated under visible light. Effects of variant swayful factors were studied for instance dosage of catalyst, concentration of dye and the incipient pH. A huge number of intermediates which yielded from photo degradation were disunited, identified, and distinguished via ultra performance to gain a well concept about the photo degradation of eosin yellowish dye assisted by ZnO and the mechanistic details related to this process which depends upon irradiation with visible light of low watt. As a photo catalyst, ZnO was depended in the current paper to perform the degradation process of eosin yellowish dye under UV light via a slurry reactor. Depending upon varying concentrations of catalyst and initial dye as (0.3 – 1.5 g/l) and (20 – 120 mg/l) respectively, different parameters optimum values were gained videlicet concentration of catalyst, initial substrate concentration that affects the eosin yellowish dye degradation rate and the type of catalyst. The diminishing of substrates and colour as concomitant with the diminution of total content of organic carbon was monitored. Keywords: Heterogeneous reaction; Eosin yellowish dye; Degradation dyes